Single‐Particle Spectroscopy on Large SAPO‐34 Crystals at Work: Methanol‐to‐Olefin versus Ethanol‐to‐Olefin Processes. Issue 34 (23rd July 2013) - Qian, Qingyun; Ruiz‐Martínez, Javier; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; van der Bij, Hendrik E.; Kornatowski, Jan; Weckhuysen, Bert M.
Abstract The formation of hydrocarbon pool (HCP) species during methanol‐to‐olefin (MTO) and ethanol‐to‐olefin (ETO) processes have been studied on individual micron‐sized SAPO‐34 crystals with a combination of in situ UV/Vis, confocal fluorescence, and synchrotron‐based IR microspectroscopic techniques. With in situ UV/Vis microspectroscopy, the intensity changes of the λ=400 nm absorption band, ascribed to polyalkylated benzene (PAB) carbocations, have been monitored and fitted with a first‐order kinetics at low reaction temperatures. The calculated activation energy (Ea) for MTO, approximately 98 kJ mol−1, shows a strong correlation with the theoretical values for the methylation of aromatics. This provides evidence that methylation reactions are the rate‐determining steps for the formation of PAB. In contrast for ETO, the Ea value is approximately 60 kJ mol−1, which is comparable to the Ea values for the condensation of light olefins into aromatics. Confocal fluorescence microscopy demonstrates that during MTO the formation of the initial HCP species are concentrated in the outer rim of the SAPO‐34 crystal when the reaction temperature is at 600 K or lower, whereas larger HCP species are gradually formed inwards the crystal at higher temperatures. In the case of ETO, the observed egg‐white distribution of HCP at 509 K suggests that the ETO process is kinetically controlled, whereas the square‐shaped HCP distribution at 650 K is indicative of a diffusion‐controlled process. Finally, synchrotron‐based IR microspectroscopy revealed a higher degree of alkylation for aromatics for MTO as compared to ETO, whereas high reaction temperatures favor dealkylation processes for both the MTO and ETO processes.